CYBERBULLYING AMONG TEENAGERS: THEORETICAL AND LEGAL ASPECTS - Orsayeva Raissa Anuarovna; Saduakasova Laila Kumarbekovna (Research Retrieval and Academic Letters, 2025)
The article provides an understanding of cyberbullying among minors and gives its theoretical and criminal-legal characteristics within the framework of the law. In the modern information society with the expansion of digital communications, a new and serious threat to psychological and emotional well-being has arisen - cyberbullying. This phenomenon is a form of aggression and harassment that is carried out via the Internet and social resources. The article describes a recently emerged and widespread type of bullying among teenagers - cyberbullying. The causes, types and consequences of this phenomenon are outlined. The authors also consider ways to prevent cyberbullying